Validity of Goods And Services Sale and Purchase Agreements by Online - Muhammad Aldi; Rahmatul Hidayati; Sunardi; Budi Parmono (Faculty of Law, University of Merdeka Malang, 2024)
The Internet is developing quickly and significantly impacts every part of life. Thanks to the Internet, people may contact, communicate, and even conduct business with anyone worldwide quickly, cheaply, and effortlessly. Buying and selling transactions through electronic media are legal agreements or relationships carried out by networking computer-based information systems and communication systems based on telecommunications networks and services. This process is further made possible by worldwide internet computer networks. International society in general and Indonesian society in particular have greatly benefited from using electronic transaction media, or e-commerce, in the trade industry. Establishing an agreement occurs when two parties come to a consensus on a primary issue that serves as the agreement's goal. To agree on what has been agreed upon, both parties must be present in a meeting of wills. It is possible to comply with wishes orally or in writing. In today's world, where technology is widely used in business, a face-to-face meeting or written agreement is no longer necessary to express wants. Agreements between parties with different legal systems that are made online are nonetheless enforceable.